Financial literacy, present bias and alternative mortgage products - Gathergood, John; Weber, Jörg (Journal of Banking & Finance, 2017)
Choosing a mortgage is one of the most important financial decisions made by a household. Financial innovation has given rise to more complex mortgage products with back-loaded payments, known as ‘Alternative Mortgage Products’ (AMPs), or ‘Interest-Only Mortgages’. Using a specially designed question module in a representative survey of UK mortgage holders, we investigate the effect of consumer financial sophistication on the decision to choose an AMP instead of a standard repayment mortgage. We show poor financial literacy and present bias raise the likelihood of choosing an AMP. Financially literate individuals are also more likely to choose an Adjustable Rate Mortgage (ARM), suggesting they avoid paying the term premium of a fixed rate mortgage.